(untitled) (Bangladesh Journal of Pharmacology, 2025)
The intention of this work was to analyze that carvacrol could enhance cancer-inhibiting potency of cetuximab (monoclonal antibody) in lung cancer cells. The combination of cetuximab and carvacrol was found to co-operatively suppress cell proliferation by enhancing apoptosis and inducing cell cycle arrest in A-549 and H1299 cells. Furthermore, the combination therapy triggered cell death by inducing membrane disruption. The most effective combinations were IC₁₀ cetuximab + IC₁₀ carvacrol for A-549 and IC₂₀ cetuxi-mab + IC₁₀ carvacrol for H1299 (CI = 2.0). LDH activity increased by 101% in A-549 and 239% in H1299 (p<0.05). Caspase-3 activity rose by 1.6-fold in A-549 and 1.4-fold in H1299 (p<0.05). The combination decreased PCNA, topo-isomerase II-alpha, and cyclins D1, D2, E, A, and B (p<0.05). Overall, the com-bination of carvacrol and cetuximab appears to enhance anti-cancer efficacy and may significantly improve therapeutic outcomes in lung cancer cells.